IL-38 Alleviates Inflammation in Sepsis in Mice by Inhibiting Macrophage Apoptosis and Activation of the NLRP3 Inflammasome - Yun Ge; Juan Chen; Yanting Hu; Xinyi Chen; Man Huang (Mediators of Inflammation)
Interleukin- (IL-) 38 is an emerging cytokine with multiple functions involved in infection and immunity. However, the potential role of IL-38 in the host immune response during sepsis remains elusive. Herein, we investigated if macrophages in septic mice express IL-38, the molecular mechanisms behind its expression, and the downstream effects of its expression. In mouse peritoneal macrophages, lipopolysaccharide (LPS) upregulated IL-38 and its receptor IL-36R, and the resulting IL-38 shifted macrophages from a M1 to M2 phenotype. Moreover, exposure to IL-38 alone was sufficient to inhibit macrophage apoptosis and LPS-driven activation of the NOD-, LRR-, and pyrin domain-containing 3 (NLRP3) inflammasome. These effects were partly abrogated by IL-38 downregulation. In septic mice, IL-38 markedly lowered serum concentrations of proinflammatory cytokines and greatly improved survival. Conversely, IL-38 blockade aggravated their mortality. Collectively, these findings present IL-38 as a potent immune modulator that restrains the inflammatory response by suppressing macrophage apoptosis and activation of the NLRP3 inflammasome. IL-38 may help protect organs from sepsis-related injury.